"Cuidado de Enfermería desde la perspectiva de la madre de pacientes pediatricos oncológicos en Trujillo. Hospital de Alta Complejidad Virgen de la Puerta" - Cerna Salazar, Cristhie Alexandra (2017)
The present qualitative study had as object of study "Nursing care from the perspective of the mother of pediatric oncology patients". The objective was to describe and analyze nursing care from the perspective of the mother of the pediatric oncology patient. The method used was the descriptive, theorized and applied by Hernandez, Fernandez and Baptista (2010), and Panqueva and Correa (2008). The scenario was the Hospital of High Complexity Virgen de la Puerta, Trujillo; with ten participants. Among the techniques used; the observation, which is realized through the direct contact of the researcher with the observed phenomenon where a variety of situations or phenomena are captured, transmitting the most imponderable of real life (Minayo, 2007). On the other hand, the in-depth interview is a personal interview, direct and unstructured, which allows the interviewee to freely express himself (Mejía, 2008; Minayo, 2007) based on dialogue, in order to codify topics, decode subtopics and Recodificar the synthesis, giving rise to two major issues generating debate: 1) Humanized care and 2) Mechanized care.